The relationship between attitude, knowledge and skill in basic accounting principles among accounting students - Maizunwati Mat Zain (Kulliyyah of Education, International Islamic University Malaysia, 2019)
The basic accounting principles is one of the courses in the Accounting curriculum which comprised the concepts of accrual, conservatism, conceptual consistency, historical cost, entity, full disclosure, concern, corresponding, materiality, financial unit, reliability, revenue recognition and time period. Students who lack understanding of basic accounting principles are usually unable to perform well in their next level of accounting discipline. Students also need to embrace the right attitude in studying this course in order to perform as required. Hence, the relationship between attitudes towards accounting practices and knowledge of accounting principles will influence the students' performance and their chances of success in practical skills application. Therefore, these issues were being focused in this research study. This study uses quantitative cross-sectional design, which applies descriptive and correlational statistical approaches in analyzing the data collected from surveys to answer the three research questions: 1) level of attitudes and knowledge in basic accounting principles as well as accounting skills of the participants, 2) relationship between some demographic aspects of the students with their attitude, knowledge and skills and, 3) relationship between the three elements of attitude, knowledge and skills. The participants of the study are 154 accounting students from Darulnaim College of Technology. The instruments developed are in the form of survey questionnaires that consist of items that examined students' attitude according to the three constructs of attitude – cognitive, affective, and behavioral. Students' knowledge of basic accounting principles was tested in another section of the questionnaire. In addition, the final score of the exam comprising 40% of the assignment (coursework) and 60% of the final exam is used to measure the students' skills in basic accounting principles. The findings show that students' attitude towards accounting principles is quite positive (Mean = 3.77 measured using a Likert scale of 1 – 5), and their knowledge is quite good (with mean score of 8.53 out of a total score of 9). It was found that female students have better attitude (especially the affective attitude component) as compared to males. The other significant finding is that female students score significantly better in knowledge of basic accounting principles as compared to males. The result also shows that students' attitude influences their knowledge of basic accounting principle. Other significant relationship found are between students' attitude and students' current Semester Study and between students' skills and interest to pursue accounting related field. However, no relationship was found between the variables of attitude, knowledge and skills. Hence, more studies of this nature are recommended in other institutions to confirm and find out the possible causes.